Cross-sectional study of visual and musculoskeletal disorders among the information technology professional workers in Bengaluru South, Karnataka, India - N. B., Swetha; ., Shobha; T. S., Ranganath; S., Shibi; Shireen, Nimra (International Journal Of Community Medicine And Public Health, 2016)
Background: India has been in the forefront in cyber world with information technology (IT) industry developing into a major service provider. Computers are the vital tool used by these IT professionals. However, the long periods of working at a computer as most people do, can cause musculoskeletal problems, eyestrain, and overuse injuries of the hands and wrists which can be reduced or eliminated with proper workstation design and improved posture. With younger generation being introduced to computers much early on in life, it is all the more important to be aware of the problems and follow necessary preventive steps to check the progression of computer related health problems. Methods: It is a cross-sectional descriptive study, conducted among the IT professionals working in IT companies of Bengaluru South zone. Based on a previous study, with musculoskeletal disorder 77.5%, 10% allowable error, sample size calculated as 120. Study was conducted during August 2015- November 2015. Results: Most of the respondents, 90.83% (109) worked on computer for 7-9 hours. Visual symptoms present in 94/120 (78.33%) of the respondents in past 6 months. Musculoskeletal symptoms present in 84/120 (70%) of respondents. Most of them, 80 (66.66%) were not trained regarding appropriate posture while working on computer. Conclusions: IT professional are of younger age and are prone to early health disorders due to long continuous working hours on computer. Majority of them are not trained in any kind of appropriate posture for working on computer.